Evaluasi Minat Belajar terhadap Hasil Belajar Mahasiswa Mata Kuliah Rekayasa Hidrologi Prodi Teknik Sipil Universitas Negeri Gorontalo - St. Marwah Fadillah Evier; Rawiyah Husnan; Frice L. Desei (Transbahasa, 2025)
Learning interest is one of the internal factors that determines students’ academic success. In the context of Hydrologic Engineering courses, which require analytical understanding, strong learning motivation is needed to participate in learning optimally. This research was conducted due to students' low learning outcomes, even though they regularly attended lectures. Therefore, this study aimed to evaluate the influence of learning interest on student learning outcomes in the hydrologic engineering course in the Civil Engineering Study Program, Universitas Negeri Gorontalo. This quantitative research, with an ex post facto approach, used all students (84 people) who had taken the hydrologic engineering course as a population and a sample (total sampling technique). Data were collected through learning interest questionnaires and academic score documentation, then analyzed using the Wilcoxon Signed Ranks Test. Based on the analysis, there was a significant relationship between learning interest and student learning outcomes. Students with a high interest in learning tend to get better academic grades. Aspects of interest, attention, and active involvement in learning have been shown to play an essential role in academic achievement. Thus, it is recommended to implement interactive and contextual learning methods and utilize supporting facilities, such as simulation software and real-life case studies, to improve student motivation and learning outcomes.